Temperature and creatine kinase changes during a 10-day taper period in sprinters - Korman, P.; Kusy, K.; Kantanista, A.; Straburzynska-Lupa, A.; Zielinski, J. (Physiological Measurement, 2021)
Objective.The aim of this prospective cohort study, performed during a 10-day training camp, was to analyze the effect of a series of successive speed-power training sessions on the concurrent circadian changes in resting leg skin temperature and blood creatine kinase (CK) levels and to determine the correlation between them. Approach. Seventeen elite sprinters, aged 22-31 years, were examined. Every morning and evening, capillary blood samples were drawn to assay CK levels. Lower limb skin temperature was measured simultaneously, and thermal images were taken using an infrared camera. Main results. From the first day of the training camp, the base temperature levels began to drop to obtain a significant reduction from the 6th day (male) and from the 8th day (female) to the end of the camp . Simultaneously, CK levels increased in the male group from 8th to the end of the camp, but it did not change significantly in females. Regarding the circadian rhythm, the CK levels always rose during the day and declined during the night. The temperature decreased during the day and increased during the night until the 6th day. After that, the temperature changed oppositely till the end of camp, i.e. it increased during the day and decreased during the night. This could suggest that the training microcycle should last about a week because after this time there may be a disturbance in the temperature circadian rhythm and a significant CK accumulation Significance. Multi-day speed-power training induced a progressive reduction in resting skin temperature and an elevation in CK levels. It also altered the circadian rhythm of the body skin temperature, which may indicate that after about 6 days of regular exercise, physiological deregulation may occur.